(untitled) (Third Sector Social Economic Review, 2022)
The main purpose of the research is to determine the factors affecting the product marketing through the cooperatives of members in the Agricultural Credit Cooperative (ACC). The primary data of this study was obtained via the face to face questionnaires from the selected 91 members of the ACC operating in Igdir province using the simple random sampling method. Binary logistic regression analysis was used to determine the factors affecting product marketing status through the members’ cooperatives. According to the results, it has been determined that 40,7% of the cooperative members participate in the product marketing process of the cooperatives, while 59,3% do not. Model results show that while satisfaction of members, education level and have a positive experience with cooperatives had statistically positive effects on the product marketing status through the members’ cooperatives; age of members had statistically negative effects. In order to increase the power of the cooperatives in the market by increasing the product marketing situation of the cooperative members through ACC, it is necessary to increase the satisfaction levels of the members with other services of the cooperative, to target the younger and the cooperative member farmers who have high school or higher education, and to carry out activities to ensure that the members have a positive experience with their cooperatives. In addition, policies should be developed to encourage youth in membership with cooperatives, and farmers who are younger and more educated should be privileged in cooperative management. In order for the organizations to be more effective in the region, it is considered necessary to provide continuous trainings on cooperatives and organization to the farmers who are or are not members of the cooperatives.